Increased Dissolution Rate of Solid Dispersion Fenofibric Acid PEG 6000 and In Vivo Study - Deni Anggraini; Nesa Agistia; Armon Fernando; Amanda Yulia; Dira Repuja (Journal of Food and Pharmaceutical Sciences, 2026)
Fenofibrate acid is a fibrate drug with high permeability but low water solubility, resulting in limited bioavailability. Solid dispersion using hydrophilic carriers is one strategy to increase solubility. The objective of this study was to improve the solubility of fenofibric acid by converting it into a solid dispersion system using PEG 6000 as a carrier. Preparation of solid dispersion systems by the melting method. The fenofibric acid PEG 6000 weight ratios were F1 (1:1), F2 (1:3), and F5 (1:5). Physicochemical characterization of the solid dispersions included DSC, PXRD, FTIR, and SEM tests, as well as dissolution and bioavailability tests with the determination of pharmacokinetic parameters. Characterization results show that fenofibric acid with PEG 6000 as a carrier still exhibits a crystalline phase but with reduced intensity, resulting in increased solubility and dissolution rate. Dissolution test show that solid dispersion F3 (1:5) dissolves faster (78.7%) than pure fenofibric acid (53.2%). after 60 minutes. Pharmacokinetic parameter determination tests showed no significant difference between pure fenofibric acid and solid dispersion. Solid dispersion of fenofibric acid with PEG 6000 as a carrier can improve the physicochemical performance and dissolution rate of fenofibric acid but pharmacokinetic parameters did not differ significantly.